The relationship between achievement motivation and college students’ general self-efficacy: A moderated mediation model - Li, Na; Yang, Ying; Zhao, Xiang; Li, Yue (Frontiers in Psychology, 2023)
Objective: This study focused on the relationship between achievement motivation and college students' general self-efficacy, and aimed to explore the mechanism of action between achievement motivation and general self-efficacy. Methods: Through convenience sampling, 1076 college students were investigated from Anhui Province in China. Achievement motivation, general self-efficacy, perceived social support, and sports participation were evaluated using standard scales. For data analysis, Pearson’s correlation analysis, structural equation model test, and bias-corrected percentile Bootstrap method were carried out.Results: Common method biases can be accepted in this study. (1) Achievement motivation can directly affect general self-efficacy and make a positive prediction; (2) Perceived social support plays a mediating role between achievement motivation and general self-efficacy, that is, achievement motivation can indirectly affect general self-efficacy through perceived social support; (3) Sports participation plays a moderating role in the first half of the mediating path of "achievement motivation → perceived social support → general self-efficacy". The interaction between achievement motivation and sports participation affects perceived social support, and then indirectly affects general self-efficacy. In this moderated mediation model, The predictive effect of achievement motivation on general self-efficacy is significantly different among individuals with different levels of sports participation. Conclusion: Perceived social support plays a part of mediating role between achievement motivation and college students' general self-efficacy, which is moderated by sports participation.